Africa and the Millennium Development Goals progress, problems, and prospects - edited by Charles Mutasa (Lanham Rowman & Littlefield, 2015)
This unique work by the Centre for Conflict Resolution (CCR), Cape Town, South Africa, tracks the progress Africa has made in achieving the United Nations? Millennium Development Goals (MDGs) since 2000.
Includes index.
Keywords: Millennium Development Goals--Africa.